Rancang Bangun Jig dan Fixture Pump Casing V(S) 2/4/6 B untuk Proses Milling pada Mesin CNC Milling Horizontal 4 Axis Double Pallet - Raul Taka Prakusya; Bayu Wiro Karuniawan; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
PT. Zenith Allmart Precisindo is one of the manufacturing companies engaged in foundry investment casting. Its superior product is pump casing V(S) 2/4/6 B which has a production target of 500pcs/month every month. The milling process for the V(S)2/4/6 B pump casing product has the disadvantage that it requires more CNC milling machines to process each part of the process. PT. Zenith Allmart Precisindo has a horizontal 4 axis double pallet CNC milling machine. This machine uses a fixture and clamp as a stopper to aid in bulk processing of casting products. In order to help the finishing process of the production of the V(S) 2/4/6 B pump casing quickly, tools such as jigs and fixtures were made, so as to speed up the process of working on V(S) 2/4/6 B products and reduce machine usage. CNC for every part of the process. Design of jig and fixture V(S) 2/4/6 B using Autodesk Fusion 360 software. The method used is the Ulrich method as a method of selecting a design concept by making 3 different concept designs. This V(S) 2/4/6 B jig and fixture produces 2 V(S) 2/4/6 B products in one milling process with 47 minutes to produce 2 products at once.